A new modular semi-parallel EIT system for medical application. (January 2018) - Ma, Yixin; Miao, Liwen; Qin, Hui; Chen, Xinyi; Xiong, Xiaofan; Han, Tao; Qin, Peng; Ji, Xiaojun; Cai, Ping
Abstract: A modular semi-parallel EIT data acquisition system (SJTU Mk-1) for medical application is newly developed. It consists of one control module and an expandable number of independent frontend modules. The control module generates stimulating signals, intermediates the communication between remote PC and frontends, and synchronize frontends during parallel data acquisition. All frontend modules are closely and symmetrically connected to electrode sensing array, so the length of signal traces can be minimized for better measurement accuracy at higher frequencies. The system can spectrum impedance from 1 kHz to 1 MHz which covers the majority frequency range of medical impedance investigations. The amplitudes of stimulating currents are limited to 0.4 mA with built-in alarm of abnormal current on each frontend module for extra safety protection. Transformers and optoelectronic couplers are used to isolate the human body under test from mains power supply and geological ground. The developed EIT Data Acquisition System (DAS) is natively safe and suitable for medical applications. To maximize number of independent measurement for better spatial resolution of reconstructed image, the sensing array is implemented with compound electrodes. System performance tests at excitation current less than 0.5 mA show that, the Signal-to-Noise Ratio (SNR) of transfer impedance is higher than 70 dB, the amplitude and phase measurement repeatability are better than 0.6% and 1° respectively. Initial phantom experiments further demonstrate the imaging capability of the developed EIT DAS for medical application.